Development of engineering drawing ability for emerging engineering education - Guo, Jian-Wen; Cao, Xiao-Chang; Xie, Li; Jin, Jian-Jun; Wang, Chu-Diao (IOP conference series. Materials Science and Engineering, 2017)
Students majoring in engineering is required by the emerging engineering education (3E) in the aspect of their ability of engineering drawing. This paper puts forward training mode of engineering drawing ability for 3E. This mode consists of three kinds of training including training in courses, training in competitions and training in actual demand. We also design the feasible implementation plan and supplies viable references to carry out the mode.